New project in communications skills - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
A proiect is underway in Kenya to train agricultural extension workers in communications skills and thus support the Kenyan Governments efforts to boost the effectiveness of the national extension services (see SPORE 23 'Communicating with...